2018
DOI: 10.1007/978-3-319-69953-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Querying Large Scientific Data Sets with Adaptable IO System ADIOS

Abstract: Abstract. When working with a large dataset, a relatively small fraction of data records are of interest in each analysis operation. For example, while examining a billion-particle dataset from an accelerator model, the scientists might focus on a few thousand fastest particles, or on the particle farthest from the beam center. In general, this type of selective data access is challenging because the selected data records could be anywhere in the dataset and require a significant amount of time to locate and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Second, the decoupled approach alleviates the metadata bottleneck of metadata servers of the underlying PFS since query operations can be handled by the external query manager. Finally, as previous studies have demonstrated, scientific data are rarely modified once they are generated, and data consistency between external KV pairs and data files can be easily maintained.…”
Section: Design and Implementationmentioning
confidence: 99%
See 4 more Smart Citations
“…Second, the decoupled approach alleviates the metadata bottleneck of metadata servers of the underlying PFS since query operations can be handled by the external query manager. Finally, as previous studies have demonstrated, scientific data are rarely modified once they are generated, and data consistency between external KV pairs and data files can be easily maintained.…”
Section: Design and Implementationmentioning
confidence: 99%
“…It may complicate the consistency issues by managing UDM and indexes as external KV pairs. However, as previous studies have demonstrated, scientific data are rarely modified once they are generated, we apply a relaxed consistency model in our current implementation. UniIndex provides encapsulated APIs (eg, setAttribute and buildIndex) and command line utilities to update external metadata objects.…”
Section: Design and Implementationmentioning
confidence: 99%
See 3 more Smart Citations